The American Literary Sculptors: A Map of the Roman Studios - Daniele Pomilio (European Journal of American Studies)
This critical account of the art studios of what was once the Roman art district, visited by the Alcott sisters during their stay in Rome in winter 1870-71, casts light on a vivid, cosmopolitan art scene through micro-biographies of the American literary sculptors trained at the school of Thorvaldsen and Canova. Among them, the unprecedented freedom experienced in Rome by the community of American sculptresses led by Charlotte Cushman contributed to their professional emancipation while producing marble representations of their republican and abolitionist values.